Phonetic Analysis: The System Of Sounds And Its (Texas Journal of Multidisciplinary Studies, 2025)
Phonetics is a critical subfield of linguistics that focuses on the study of sounds in human speech. This paper explores the system of sounds and its functions in human language, particularly within the scope of phonetic analysis. The study includes the classification of speech sounds, their articulation, and their role in communication. It aims to illustrate how phonetic systems serve various linguistic purposes, including speech production, perception, and phonological processing. The paper emphasizes how phonetic analysis can help in understanding language structure and function, as well as the practical applications of phonetics in language teaching, speech therapy, and phonological research